Afterword: comparative versus historical research. (2nd January 2019) - Jasper, James M.
ABSTRACT: The articles in this special issue represent the triumph of detailed historical research over an older version of comparative research that was too eager to reduce complex settings to correlations among a few variables. While the events in MENA starting at the end of 2010 revived interest in revolutions, they also suggested new ways of thinking about revolutions, or rather about the long chains of interactions that may or may not lead to regime change. Emotions, individuals, identities, networks and much more help us see the interactions among players in a variety of formal and informal arenas.